Analisis Penetapan Jadwal Waktu Salat Subuh Wahdah Islamiyah - Andi Muhammad Akhyar; Sirajuddin Sirajuddin; Azwar Azwar; Aswar Aswar; Andi Muhammad Akmal (JURNAL AT-TURAS, 2022)
The inclusion of prayer time is one of the valid requirements of prayer as explained in the Qur'an and hadiths of the Prophet (s). The Fajr prayer schedule issued by Wahdah Islamiyah is interesting to review because it is different from the official prayer schedule issued by the Ministry of Religious Affairs, Republic of Indonesia. This difference can have implications for the validity or absence of Fajr prayers and fasting performed by Muslims based on the schedule. This study aimed to analyze the method of determining the Fajr prayer schedule issued by Wahdah Islamiyah. This research is qualitative descriptive research through library study methods and content analysis. The results showed that Wahdah Islamiyah compiled its Fajr prayer schedule with a high-accuracy contemporary accounting method using VSOP87 algorithm. The location of markaz da'wah in Makassar City was chosen as the coordinate point of the calculation of the position of the sun. Wahdah Islamiyah's Fajr prayer schedule uses a sun altitude of 18 degrees below the horizon by adding a two-minute of iḥtiyāṭ. Based on the calculation, the Fajr prayer schedule of Wahdah Islamiyah has been accurately used in the Makassar City area